2017
DOI: 10.1007/s00394-017-1423-1
|View full text |Cite
|
Sign up to set email alerts
|

Greater adherence to the dietary approaches to stop hypertension (DASH) dietary pattern is associated with lower blood pressure in healthy Iranian primary school children

Abstract: The findings suggest that greater adherence to the DASH dietary pattern is associated with lower BP in healthy Iranian primary school children. However, future prospective studies of adequate methodological quality are warranted to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
2
5
0
Order By: Relevance
“…The modified DASH diet might have greater positive or negative effects in combination with antihypertensive treatment or have higher accordance or provision of different interventions, such as dietary advice or food supplements, however, we did not have sufficient data for these analysis. Like previous studies (31)(32)(33), we found that the modified DASH diet was significantly associated with reductions in SBP, DBP, and cardiovascular risk factors. However, some discrepancies in the degree of BP and cardiovascular risk factor reduction were found.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The modified DASH diet might have greater positive or negative effects in combination with antihypertensive treatment or have higher accordance or provision of different interventions, such as dietary advice or food supplements, however, we did not have sufficient data for these analysis. Like previous studies (31)(32)(33), we found that the modified DASH diet was significantly associated with reductions in SBP, DBP, and cardiovascular risk factors. However, some discrepancies in the degree of BP and cardiovascular risk factor reduction were found.…”
Section: Discussionsupporting
confidence: 84%
“…Like previous studies ( 31 33 ), we found that the modified DASH diet was significantly associated with reductions in SBP, DBP, and cardiovascular risk factors. However, some discrepancies in the degree of BP and cardiovascular risk factor reduction were found.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We found no effect of MDASH score on SBP nor DBP, despite many studies have shown its association with BP, mainly in adults. In Iranian children, DASH score measured with a semiquantitative FFQ was associated with lower SBP values [22,42]. Other study in US youth showed an inverse association between DASH score and DBP, but DASH was measured by 24h recalls and with nine target nutrients [43].…”
Section: Discussionmentioning
confidence: 88%
“…Given the association between food intake and BP, dietary recommendations such as the Dietary Approach to Stop Hypertension (DASH) have been described as potential preventive strategies against high BP and cardiovascular disease in children and adults [18][19][20][21][22]. The DASH diet consists on a high consumption of fruits, vegetables, legumes, nuts, whole grains, low-fat dairy products, fish, chicken and a low consumption of red meat and SSBs [18,19].…”
Section: Introductionmentioning
confidence: 99%